Disharmonisasi Periode Pemberlakuan Rencana Induk Pembangunan Kepariwisataan Daerah di Indonesia (Implementasi Peraturan Pemerintah Nomor 50 Tahun 2011 tentang Rencana Induk Pembangunan Kepariwisataan) - Rifan, Mohamad; Fikriya, Hilmi Inaya (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2021)
Regional autonomy brings consequences for each region to take care of and explore its potentials. Moreover, the region is given options to manage the tourism sector which is potential to optimize the development of the district. The composition of tourism in Indonesia consists of regional up to national levels by concerning the diversities, uniqueness, and peculiarities of its culture and nature. Consequently, as mentioned in Act No. 10 of the year 2009 concerning tourism of article 8 mentioned that tourism development is conducted based on the master plan for tourism development is an integral part of the national long-term development plan. Therefore, the planning duration of RIPPARPROV and RIPPARKAB/KOTA also adjusts to the period of the Regency/city long-term development plan which is the period is same as the national long-term development plan (RPJP). However, the implementation of tourism law is not optimal due to some of the main tourism plans having disharmony on the scale of its validity periods such as RIPPAR-Prov East Java and Central Java, or RIPPAR-Kota Surakarta and Balikpapan. Through the Yuridis-normative research method and the approach of statutory and conceptual regulations, researchers focus on analyzing the consequences of the disharmony of the main tourism plan base on 3 (three) theories of law which are synchronization theory, harmonization theory, and legal development theory.